Carbon nanotube- and graphene-based nanomaterials and applications in high-voltage supercapacitor: A review. (January 2019) - Yang, Zhoufei; Tian, Jiarui; Yin, Zefang; Cui, Chaojie; Qian, Weizhong; Wei, Fei
Abstract: The use of carbon nanotube- and graphene-based nanomaterials as a high-performance electrode is one of the promising directions when it comes to developing high-voltage supercapacitors with both a high power density and high energy density. However, the mass production and post-treatment of the carbon nanotube/graphene-based nanomaterials with high purity are necessary steps toward the commercialization of high-performance supercapacitors, and the challenges in engineering carbon nanotube/graphene-based nanomaterials for device-scale supercapacitors also need to be considered. In this review, the authors first introduce the chemical vapor deposition for large-scale preparation of carbon nanotube/graphene-based nanomaterials and the exfoliation method for graphene, which are followed by the methods used to purify these nanomaterials. Then, the capacitance performance of the carbon nanotube/graphene-based nanomaterials in the electrolytes of a high-voltage window is discussed, including the discussion of the capacitance limit of sp 2 carbon materials, as well as a comparison of the capacitance performance in ionic liquids electrolytes with that in organic electrolytes and a discussion of low-temperature performance. Finally, the challenges in fabricating supercapacitor devices, such as the intake of excess liquids, the densification of carbon nanotube/graphene-based electrodes, and the reduction of the resistance of supercapacitors, are addressed. Graphical abstract: The use of carbon nanotube- and graphene-based nanomaterials as the high-performance electrode is supposed to be one of a promising direction to develop high-voltage supercapacitor with both high power density and high energy density. In this review, the chemical vapor deposition and the exfoliation methods for the large-scale preparation of carbon nanotube, graphene and their hybrids were reviewed, and the purification methods to remove metal impurities and oxygen-containing functional groups were introduced. Then the capacitance performance of the carbon nanotube/graphene-based nanomaterials in electrolytes of high voltage window was discussed, including the comparison with the organic electrolyte and the discussion of low-temperature performance. The methods in fabricating supercapacitor device including the intake of excess liquids, the densification of carbon nanotube/graphene-based electrode and the reduction of resistance of supercapacitor are also addressed. Image 1